PERAN KELUARGA, SEKOLAH, DAN MASYARAKAT DALAM PEMBENTUKAN KARAKTER BERKUALITAS - Rahmayanty, Dinny; Lailatul Khasanah, Umi; Herawati Emosda, Ratna; Putri Rinjani, Annisa; Anggraini, Dinda (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
To rebuild national identity and encourage the formation of a new Indonesian society, character education is an important and strategic step. This research uses a library approach. The results of this study show that building student character is not easy and not fast. To be reflective and practical, it requires continuous effort and deep reflection to make a series of moral decisions that must be followed up with concrete actions.It takes time for all of this to become a habit and become a person's character or character.The character of education must involve various elements: society, school environment, family and household. Reconnecting educational relationships and networks that are almost broken between these three educational environments is the main step that must be taken